Physical Properties and Gas Hydrate at a Near‐Seafloor Thrust Fault, Hikurangi Margin, New Zealand. Issue 16 (17th August 2020) - Cook, Ann E.; Paganoni, Matteo; Clennell, Michael Benedict; McNamara, David D.; Nole, Michael; Wang, Xiujuan; Han, Shuoshuo; Bell, Rebecca E.; Solomon, Evan A.; Saffer, Demian M.; Barnes, Philip M.; Pecher, Ingo A.; et al.
Abstract: The Pāpaku Fault Zone, drilled at International Ocean Discovery Program (IODP) Site U1518, is an active splay fault in the frontal accretionary wedge of the Hikurangi Margin. In logging‐while‐drilling data, the 33‐m‐thick fault zone exhibits mixed modes of deformation associated with a trend of downward decreasing density, P ‐wave velocity, and resistivity. Methane hydrate is observed from 30 to 585 m below seafloor (mbsf), including within and surrounding the fault zone. Hydrate accumulations are vertically discontinuous and occur throughout the entire logged section at low to moderate saturation in silty and sandy centimeter‐thick layers. We argue that the hydrate distribution implies that the methane is not sourced from fluid flow along the fault but instead by local diffusion. This, combined with geophysical observations and geochemical measurements from Site U1518, suggests that the fault is not a focused migration pathway for deeply sourced fluids and that the near‐seafloor Pāpaku Fault Zone has little to no active fluid flow. Plain Language Summary: Faults are boundaries in the Earth where two different blocks of sediment or rock slide past each other. Offshore New Zealand, the Pāpaku Fault is very shallow and intersects the seafloor but connects to deeper faults kilometers below the seafloor where large earthquakes can occur. An ice‐like form of methane called hydrate also occurs within and surrounding the fault. We use scientific drilling data to understand the physical properties of the fault. Hydrate can affect fault properties and how fluid flows; however, based on the pattern of hydrate distribution and other geochemical and geophysical measurements, we suggest that the Pāpaku Fault does not have active fluid flow. Key Points: The Pāpaku Fault Zone is a 33‐m‐thick near‐seafloor splay fault drilled at Site U1518 on the Hikurangi Margin Multiple lines of observational, geophysical, and geochemical evidence suggest that there is little to no fluid flow along the Pāpaku Fault